Judging Judges: A Study of U.S. Federal District Court Judges in the 10th Circuit - Eli Wald (Oñati Socio-Legal Series)
This paper examines the demographics of federal district court judges in the 10th Circuit. Consistent with the glass-ceiling effect literature in positions of power and influence in the legal profession, the study finds that women judges are under-represented on the 10th Circuit bench compared with their numbers as lawyers in the jurisdictions of the Circuit. However, the study finds that minority judges are over-represented in the Circuit. The paper next explores the relationship between under-representation, over-representation and discrimination. Under-representation that cannot be explained in terms of merit criteria or informed opting out, such as the under-representation of women on the 10th Circuit, strongly suggests the lingering effects of past exclusion and discrimination, as well as the current effects of implicit bias. As demonstrated by the over-representation of minority judges, the political commission process can break through the gender glass-ceiling by over-representing qualified women judges in the short run until their overall numbers better reflect equality.